What is the biochemical and physiological rationale for using cold-water immersion in sports recovery? A systematic review - Bleakley, C. M.; Davison, G. W. (British Journal of Sports Medicine, 2010)
Cold-water immersion (CWI) is a popular recovery intervention after exercise. The scientific rationale is not clear, and there are no clear guidelines for its use. The aim of this review was to study the physiological and biochemical effect of short periods of CWI. A computer-based literature search, citation tracking and related articles searches were undertaken. Primary research studies using healthy human participants, immersed in cold water (<15°C), for 5 min durations or less were included. Data were extracted on body temperature, cardiovascular, respiratory and biochemical response. 16 studies were included. Sample size was restricted, and there was a large degree of study heterogeneity. CWI was associated with an increase in heart rate, blood pressure, respiratory minute volume and metabolism. Decreases in end tidal carbon dioxide partial pressure and a decrease in cerebral blood flow were also reported. There was evidence of increases in peripheral catecholamine concentration, oxidative stress and a possible increase in free-radical-species formation. The magnitude of these responses may be attenuated with acclimatisation. CWI induces significant physiological and biochemical changes to the body. Much of this evidence is derived from full body immersions using resting healthy participants. The physiological and biochemical rationale for using short periods of CWI in sports recovery still remains unclear.